Alternative Current Conductivity Mechanism of BAC Doped Nematic Liquid Crystals - Canli, N. Yilmaz; Ozdemir, Z. Guven; Okutan, M.; Eran, B. Bilgin (AMER SCIENTIFIC PUBLISHERS, 2015)
In this work, ac conductivity and electronic properties of 5CB and 5CB (4-cyano-4'-pentylbiphenyl) (1%) BAC(4-[4-(S)-2-methylbutoxybenzoyloxy]benzoic acid) have been investigated by impedance spectroscopy within the frequency interval of 5 Hz-13 MHz. The frequency dependence of ac conductivity (sigma(ac)) of the related liquid crystals have been analyzed by means of frequency exponent parameter, s. It has been observed that adding BAC to 5CB increases the s parameter for low and high frequency regions. It has also been revealed that 5CB and 5CB + (1%)BAC composites obey dc conductivity and super linear power law (SLPL) in the low and high frequency regions, respectively. The transition frequencies, at which conductivity law changes, decrease with doping BAC for all dc bias. While the dominant electronic property of the liquid crystal composites has been determined as capacitive behavior, it has been understood that doping BAC to 5CB increases the frequency interval where the system behaves as a capacitive component for high dc bias.
Keywords: Liquid Crystal; 4-cyano-4 '-pentylbiphenyl; 4[4-(S)-2-Methylbutoxybenzoyloxy]; Benzoic Acid; AC Conductivity; Impedance Spectroscopy; FREQUENCY-DEPENDENT CONDUCTIVITY; DIELECTRIC-RELAXATION; AC-CONDUCTIVITY; Engineering; Science & Technology - Other Topics; Physics